The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/0976-9668.166088
|View full text |Cite
|
Sign up to set email alerts
|

Predebridement wound culture in open fractures does not predict postoperative wound infection: A pilot study

Abstract: Background:There is confusion in the current literature regarding the value of obtaining predebridement wound cultures in the management of open fractures with several studies reporting contrasting results. We undertook a pilot study to determine the initial bacterial flora of open fractures in our environment and determine the correlation between subsequent wound infection if any, and the initial bacterial flora.Materials and Methods:Initial/predebridement wound swabs were obtained for 32 patients with open f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Low pressure pulsatile lavage with normal saline is preferred as it has less harmful effects on tissues 27 . The practice of obtaining routine cultures from the wound either pre-or post-debridement is no longer advocated 28 .…”
Section: Irrigation and Debridementmentioning
confidence: 99%
“…Low pressure pulsatile lavage with normal saline is preferred as it has less harmful effects on tissues 27 . The practice of obtaining routine cultures from the wound either pre-or post-debridement is no longer advocated 28 .…”
Section: Irrigation and Debridementmentioning
confidence: 99%
“…En dicho estudio se determin贸 que la flora inicial no son los mismos organismos infecciosos en las heridas de fractura e440 abierta, y los cultivos de heridas previas al desbridamiento no tienen valor en la infecci贸n de la herida posterior al desbridamiento. Por lo tanto, no se recomiendan los cultivos de heridas antes del desbridamiento quir煤rgico (16).…”
Section: Cultivo De Heridaunclassified
“…Before 1980, wound bacterial culture was routinely performed before surgical debridement [ 8 , 9 ]. However, recent studies have shown that since the pathogens observed in general wound infections on land are usually acquired in the hospital, wound bacterial culture before debridement for the prediction of wound infection after debridement is not as valuable [ 10 , 11 ]; therefore, cephalosporins are often used in the early stage [ 12 , 13 ]. While the correlation between pathogenicity and seawater bacteria is strong after open trauma following seawater immersion, the correlation with pathogens in the hospital is weaker [ 7 ].…”
Section: Introductionmentioning
confidence: 99%